The Effect Of Social Support Perception On Homesickness In Away From My Own Students at HKBP Nommensen University Medan - Gultom, Jesika; Simbolon, Hotpascaman (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to determine the Influence of Perceived Social Support on Homesickness in Migrant Students at HKBP Nommensen University Medan. So the hypothesis that has been proposed can be accepted, meaning, the higher the social support received by migrant students, the lower the level of homesickness experienced by migrant students at HKBP Nommensen University Medan. From the results of categorization based on variables, it can be seen that in the Social Support variable, the majority of migrant students at HKBP Nommensen University Medan are in the moderate category, namely 88 respondents out of a total of 170 people. Furthermore, based on the results of categorization on the Homesickness variable, it is known that most migrant students at HKBP Nommensen University Medan are also in the moderate category, namely 111 respondents. The results of data analysis show that the empirical average value of social support is higher than the hypothetical average, while the empirical average of homesickness is lower than the hypothetical average. This indicates that migrant students tend to have fairly good social support and experience relatively low homesickness. Based on demographic characteristics, the highest social support was found among 21-year-old students, graduating class of 2021, from the faculties of agriculture and teacher training and education, and from North Tapanuli. Meanwhile, the highest homesickness was found among 19-year-old students, graduating class of 2024, from the faculties of medicine and teacher training and education, and from Riau.